Impact of Books and Cartoons on Developing Children's Behavior - Iskanderova Shirin Daniyarovna (Researchparks Publishing, 2024)
Books and cartoons are two of the most popular entertainment for children. While books are known for their ability to stimulate the imagination and develop literacy skills, cartoons are known for their colorful and entertaining visuals. However, the influence of books and cartoons on children's behavior is the subject of much debate. Some argue that books have a greater impact as they encourage critical thinking and promote positive values, while others argue that cartoons have a stronger impact due to their ability to captivate and entertain young minds. In this article we will look at this topic and try to determine which of these two tools has the greatest impact on children's behavior.